Collection development procedure adopted for acquisition of EIRs across agricultural libraries of northern India. (14th December 2018) - Bhat, Nazir Ahmad; Ganaie, Shabir Ahmad
Abstract : Purpose: The purpose of this paper is to explore the change(s) brought about by the advent of electronic information resources in the overall collection development process across agricultural libraries of northern India. Design/methodology/approach: A survey was conducted in 2015 by using a questionnaire as a data collection tool. The investigator also interacted with the librarians through telephone and also availed the e-mail service for required correspondence. Findings: There is a major change in the identification, selection and acquisition procedures across agricultural libraries of northern India, as the majority of these libraries are seen to adhere to an onsite demo of products and services, as the publishers/vendors to set online trial for ample of time before any decision is taken. The libraries are also seen to take advantage of e-mail correspondence to identify, select and acquire best possible information products against utmost economical costs. The responsibility of identifying and selecting the required items devolves mainly with scientists/subject experts, whereas the requisitions of students and suggestions of library staff are comparatively taken as lesser cognisance, while executing this job Library advisory committee is the most prominent authority responsible for final approval of the purchase of e-resources, while "Heads of Divisions" also play a considerable role in this regard. Research limitations/implications: Only seven agricultural libraries have been taken as a sample. Moreover, the work is confined to only four aspects, i.e. the identification, selection and acquisition procedures adopted and the authorities responsible for carrying out the job. Other aspects like that of adoption of proper collection development; policy and the criteria used for selection; and acquisition of information also need to be studied. Similar studies need to be conducted in other parts of India and also across libraries of other domains of knowledge. Originality/value: This is a first work of its nature in northern India with its domain as agricultural libraries. The findings will help the librarians and the library advisory committees to decide on logical grounds about the identification, selection and acquisition procedures adopted at present and look forward for bringing about the uniformity and improvement in the process and make changes in the policy to make room for efficient acquisition of information resources.